Internalization of Islamic character values in secondary education contexts: A systematic literature review - Randina, Elpira; Lubis, Ali Musa (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study employed a Systematic Literature Review (SLR) approach to comprehensively examine the trends, methods, success factors, and impact of internalizing Islamic character values among secondary education contexts during the period 2021–2026. The study was motivated by concerns over moral degradation among adolescents, which is reflected in the increasing number of cases of bullying and other behavioral problems in educational settings. Using the PRISMA protocol, 10 Scopus-indexed articles and 2 SINTA articles were systematically reviewed and analyzed. These findings demonstrate a shift from conventional cognitive-theoretical approaches to holistic, integrative models that combine contextual learning, teacher role modeling, habituation, and collaboration across three educational environments: school, family, and community. The review also highlights the strategic role of teacher and student intrinsic motivation as an important factor in ensuring the internalization of meaningful values and preventing superficial adherence. Furthermore, strengthening the Islamic concepts of muraqabah and tabayyun contributes to students' moral resilience in the era of digital disruption. Overall, the findings suggest that systematic value internalization promotes spiritual development, positive behavior, and moral integrity.